2017
DOI: 10.1039/c7ra11349h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of aniline-dimer-based electroactive benzoxazine and its polymer

Abstract: Benzoxazine incorporating an aniline dimer in its structure has satisfactory electroactivity and undergoes both amine-catalyzed and autocatalytic polymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The positive E corr shi from anodic to cathodic with lower values of corrosion current can be attributed to a decrease in the oxygen concentration at the metal surface and a greater barrier effect against dissolved ions in water, which arises from the higher cross-linking density, less porous nature, compact molecular structure and better compatibility with MS plates. 66 From the results obtained, it is suggested that the PET bottle waste-based epoxy blended biophenolic benzoxazine composites developed in the present work can be used as coating materials for high performance industrial applications.…”
Section: Rtmentioning
confidence: 71%
“…The positive E corr shi from anodic to cathodic with lower values of corrosion current can be attributed to a decrease in the oxygen concentration at the metal surface and a greater barrier effect against dissolved ions in water, which arises from the higher cross-linking density, less porous nature, compact molecular structure and better compatibility with MS plates. 66 From the results obtained, it is suggested that the PET bottle waste-based epoxy blended biophenolic benzoxazine composites developed in the present work can be used as coating materials for high performance industrial applications.…”
Section: Rtmentioning
confidence: 71%
“…34 To ensure that 1,4-BCBA can completely react with amine cross-linkers to form reversible units during the curing process, suitable curing conditions were determined to separate the reaction process of amine-catalyzed BA-a from that of amines with 1,4-BCBA. 36 First, to investigate the effect of the reaction between primary amine and BA-a on the conversion of 1,4-BCBA during the low-temperature curing of the blends, the BA-a/1,4-BCBA/TEAE and BA-a/1,4-BCBA samples were heated at 60 °C for 1 h. The results of 13 C NMR analysis on the postreaction samples are shown in Figure 1. After curing BA-a/1,4-BCBA for 1 h at 60 °C, the 13 C NMR analysis of the blended system (Figure 1a) showed no change in the C�O carbon signal peak.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In contrast, the poly(oPP-BZ) 180 coating had the lowest value of Q dl of 0.069 ± 0.03 µΩ −1 •s n •cm 2 . A higher value of R ct and a lower value of Q dl always correspond to better corrosion resistance performance, because of the inhibited access of water molecules to the metal surface (through the adsorption of the organic molecules) and a less active dissolution reaction [29,68]. In addition, we suspect that the change in the coating resistance (R p ) was mainly due to the change in the penetration permeability of the electrolyte through the porous coating.…”
Section: Corrosion Resistance Of Ms: Uncoated and Coated With Poly(ppp-bz) And Poly(opp-bz)mentioning
confidence: 97%
“…The incorporation of particular functional groups into PBZ coatings can enhance their adhesion to metal substrates and improve the corrosion resistance; for example, the charge transfer resistance (R ct ) of MS coated with a silane-based PBZ (1.2891 MΩ•cm 2 ) was higher than that of the uncoated MS (0.0396 MΩ•cm 2 ) [27]. Recently, PBZ-based electroactive species have been used to form protective passive oxide layers on steel substrates to prevent their corrosion [28][29][30]. For example, coating MS with PBA-ddm has resulted in excellent corrosion resistance and a decrease in the corrosion current by two orders of magnitude relative to that of the uncoated MS [31].…”
Section: Introductionmentioning
confidence: 99%